Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms222312933
|View full text |Cite
|
Sign up to set email alerts
|

Malignant and Benign T Cells Constituting Cutaneous T-Cell Lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is a heterogeneous group of non-Hodgkin lymphoma, including various clinical manifestations, such as mycosis fungoides (MF) and Sézary syndrome (SS). CTCL mostly develops from CD4 T cells with the skin-tropic memory phenotype. Malignant T cells in MF lesions show the phenotype of skin resident memory T cells (TRM), which reside in the peripheral tissues for long periods and do not recirculate. On the other hand, malignant T cells in SS represent the phenotype of central memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…MF and SzS cell phenotypes exhibit significant heterogeneity [ 6 , 7 ], and although MF cells typically exhibit a TEM phenotype and are confined to the skin while SzS cells typically exhibit a TCM phenotype and move through the peripheral blood, skin, and lymph nodes, a recent study found no correlation between disease and the phenotype of the cell of origin [ 4 , 5 , 17 ]. Further, studies have shown characteristic ultraviolet (UV) light-associated mutations in both MF and SzS cells, suggesting that these cells acquire mutations in the skin before clonal proliferation [ 17 ].…”
Section: Biomarkers Of Mf and Szsmentioning
confidence: 99%
See 1 more Smart Citation
“…MF and SzS cell phenotypes exhibit significant heterogeneity [ 6 , 7 ], and although MF cells typically exhibit a TEM phenotype and are confined to the skin while SzS cells typically exhibit a TCM phenotype and move through the peripheral blood, skin, and lymph nodes, a recent study found no correlation between disease and the phenotype of the cell of origin [ 4 , 5 , 17 ]. Further, studies have shown characteristic ultraviolet (UV) light-associated mutations in both MF and SzS cells, suggesting that these cells acquire mutations in the skin before clonal proliferation [ 17 ].…”
Section: Biomarkers Of Mf and Szsmentioning
confidence: 99%
“…In contrast, SzS cells frequently have central memory T cells (TCM) phenotype [ 4 ]. Those differences were thought to account for the distinctions in the behavior and progression of MF and SzS [ 5 ]. However, recent studies have shown that the corresponding markers of malignant T cells may change during the course of the disease, not only between patients who carry the same diagnosis, but also with some level of heterogeneity within the same patient [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the frequency and abundance of regulatory T cells (Tregs) and Th17 cells shown to accompany disease progression. Production of pro-inflammatory, anti-tumor, and tumor-promoting effector molecules demonstrated for each cell type as previously reviewed elsewhere [ 23 , 37 , 55 ]. The figure was generated using BioRender software.…”
Section: The Tumor Microenvironment (Tme) and Immune Response In Ctclmentioning
confidence: 99%